2021
DOI: 10.1186/s12884-021-03712-w
|View full text |Cite
|
Sign up to set email alerts
|

Gestational hypertension and progression towards preeclampsia in Northern Ethiopia: prospective cohort study

Abstract: Background Preeclampsia (PE) is one of the main causes of medical complication of pregnancy and is the main cause of perinatal mortality and morbidity. It is one of the top causes of maternal mortality in Ethiopia. Also known as transient hypertension, gestational hypertension (GH) is increased blood pressure during pregnancy without proteinuria, which is expected to return to normal by the 12th-week postpartum visit. PE is GH with proteinuria and /or other systemic manifestations. Evidence fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“…It has been reported that the elevation of hematocrit and Hb levels increases blood viscosity and that increased viscosity through an effect on blood pressure may partly worsen cardiovascular function [28]. Another utility of this association lies in the early detection of high gestational hypertension risk pregnancies, prompting closer follow-ups and more intensive interventions to decrease its consequences on pregnant women, including progression to PE [29]. Other adverse effects of gestational hypertension include increased risk of cesarian delivery, preterm delivery, and intrauterine growth restriction [30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the elevation of hematocrit and Hb levels increases blood viscosity and that increased viscosity through an effect on blood pressure may partly worsen cardiovascular function [28]. Another utility of this association lies in the early detection of high gestational hypertension risk pregnancies, prompting closer follow-ups and more intensive interventions to decrease its consequences on pregnant women, including progression to PE [29]. Other adverse effects of gestational hypertension include increased risk of cesarian delivery, preterm delivery, and intrauterine growth restriction [30].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 180 women were included in each study group (a ratio of 1:1); the sample size was calculated on the basis of previous data on the history (43.0%) of spontaneous abortions among women with preeclampsia in neighboring Ethiopia [ 6 ]. Therefore, we assumed that 40.0% of women with a history of spontaneous abortion would have preeclampsia and 25.0% of women with a history of spontaneous abortion would not have preeclampsia.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, most these studies have been conducted in high-income countries [ 7 , 9 , 13 , 16 ]. There is a scarcity of data on the history of abortion and preeclampsia in sub-Saharan African countries [ 6 ], and none of these studies have been conducted in Sudan. The risk factors for preeclampsia may differ in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…Gestational or pregnancy-induced hypertension, which affects up to 10% of pregnant women, is recognized by all societies as new-onset blood pressure (BP) ≥ 140/90 mmHg at or after 20 gestational weeks. The risk of progression to PE is estimated as 17.1–25% [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. About 50% of patients with gestational hypertension continue to have high BP levels after delivery.…”
Section: Definitionsmentioning
confidence: 99%